2012
DOI: 10.4103/2229-5151.97270
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of long-term infusion of dexmedetomidine in critically ill patients: A retrospective analysis

Abstract: Background:Dexmedetomidine is an α2-receptor agonist used for sedation in the intensive care unit (ICU). It is currently FDA indicated for short-term use (i.e., less than 24 h).Objectives:To compare the safety and efficacy of dexmedetomidine if given long- term (>24 h) to short-term infusion (up to 24 h) for mechanically ventilated critically ill patients.Materials and Methods:The medical records of 73 patients were evaluated. Primary outcomes were significant changes in blood pressure or heart rate. Secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…Many adult studies have demonstrated the safety of dexmedetomidine use longer than 24 hours (26)(27)(28)(29), and limited pediatric studies show a similar safety profile of long-term dexmedetomidine to that of adults (8,10,12,20,22). Our study mirrors the findings of both the adult and the pediatric data.…”
Section: Discussionsupporting
confidence: 91%
“…Many adult studies have demonstrated the safety of dexmedetomidine use longer than 24 hours (26)(27)(28)(29), and limited pediatric studies show a similar safety profile of long-term dexmedetomidine to that of adults (8,10,12,20,22). Our study mirrors the findings of both the adult and the pediatric data.…”
Section: Discussionsupporting
confidence: 91%
“…It is our practice to use dexmedetomidine as the primary sedative agent because it exhibits neurocognitive protective effects and is associated with a decreased incidence of delirium compared to other commonly used sedatives 34–36 . Its excellent safety record—less respiratory depression and superior sympatholysis compared to other sedatives—is another advantage of its use in the elderly 35,37–41 . Dexmedetomidine produces a “cooperative sedation” that mimics natural sleep; thus, patients are easily arousable and are less prone to startling from waxing and waning states of consciousness, a phenomenon often observed with the use of propofol 38,40,42 …”
Section: Discussionmentioning
confidence: 99%
“…Due to a lack of central depression, dexmedetomidine is an attractive sedative clinically for weaning from mechanical ventilation and awake sedation in non-intubated patients. Dexmedetomidine was licensed by the Food and Drug Administration as a sedative with a 24-h time limit; however, studies have shown that it is safe and effective for up to 5 d with bradycardia and hypotension being the most commonly reported adverse effects[ 4 , 9 - 11 ]. Other drawbacks have included the cost of drug acquisition and availability only in an IV formulation[ 12 - 14 ].…”
Section: Introductionmentioning
confidence: 99%